What limits college success? A review and further analysis of Holzer and Baum's 'Making College Work' - Philip Oreopoulos (Institute of Labor Economics (IZA), 2019)
Holzer and Baum's recent book, 'Making College Work: Pathways to Success for Disadvantaged Students,' provides an excellent up-to-date review of higher education. My review first summarizes its key themes: 1) who gains from college and why? 2) mismatch and the need for more structure; 3) problems with remediation; 4) financial barriers and 5) the promise of comprehensive support. I then critique the book's proposed solutions using some of my own qualitative and quantitative data. Some recommendations are worth considering, while others are too expensive or unlikely to make a meaningful difference without addressing the underlying lack of preparedness and motivation of college students. I argue that making mandatory some existing services, such as application assistance and advice, proactive tutoring and advising, and greater career transition support, has the most immediate potential.
Keywords: I2; J24; 330; college student achievement; returns to college; higher education policy; signaling